2021
DOI: 10.1155/2021/1578653
|View full text |Cite
|
Sign up to set email alerts
|

Central Obesity and Associated Factors among Adult Patients on Antiretroviral Therapy (ART) in Armed Force Comprehensive and Specialized Hospital, Addis Ababa, Ethiopia

Abstract: Background. Similar to the general population, the prevalence of central obesity is increasing among HIV-infected persons. There are little data on the burden of abdominal obesity using the waist-to-hip ratio measurement in HIV-infected patients in resource-limited settings, including Ethiopia. Therefore, this study aimed to assess the prevalence and associated factors of central obesity among HIV patients taking ART in an armed force comprehensive and specialized hospital, Addis Ababa, Ethiopia. Methods. A cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…All included studies were employed by cross-sectional study design. Of these, five studies were community-based, whereas 15 were institutional-based cross-sectional studies: six studies in Amhara (25,(33)(34)(35)(36)(37), five studies in Addis Ababa (38)(39)(40)(41)(42), three studies in Tigray (43)(44)(45), two studies in Oromia (46,47), two studies in Dire Dawa (26,48), one study in Southern Nations Nationalists and Peoples Region (49), and one study in Harari (50). The sample sizes ranged from 225 to 1,935.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…All included studies were employed by cross-sectional study design. Of these, five studies were community-based, whereas 15 were institutional-based cross-sectional studies: six studies in Amhara (25,(33)(34)(35)(36)(37), five studies in Addis Ababa (38)(39)(40)(41)(42), three studies in Tigray (43)(44)(45), two studies in Oromia (46,47), two studies in Dire Dawa (26,48), one study in Southern Nations Nationalists and Peoples Region (49), and one study in Harari (50). The sample sizes ranged from 225 to 1,935.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…Increasing BMI along with advancing age were found to be predictors of dyslipidemia, which is supported by previous studies. 13 , 49 , 50 Our study revealed more dyslipidemia than some comparative studies which show that risk of future cardiovascular disease with increasing age and longevity is high and needs urgent preventative measures. 49 …”
Section: Discussionmentioning
confidence: 52%
“…Similar results had been reported in a study conducted in Addis Ababa, which showed that AZT+3TC+EFV based medication was significantly associated to overweight/obesity. 28 On the contrary, this finding is not supported by comparative clinical trial studies, which revealed that participants taking INSTIs experienced the most weight gain than NNRTI and protease inhibitor (PI). 29 Similarly, this finding is also not in line with another follow up study which stated that Dolutegravir is associated with more weight gain than Efavirenz.…”
Section: Discussionmentioning
confidence: 95%
“…This finding is supported by the study done in Addis Ababa on the magnitude of central obesity and associated factors among adult patients on ART in armed force comprehensive and specialized hospital showed that being male was identified as a risk factor to develop obesity. 28 However, it is not supported by the cohort study done in USA and Canada that stated that women with HIV experience a significantly greater increase in BMI following ART initiation than men. 24 The possible explanation for the discrepancy might be difference of the population, socio economic status and ART drug type.…”
Section: Discussionmentioning
confidence: 96%